Optimization of medium compositions favoring butanol and 1,3-propanediol production from glycerol by Clostridium pasteurianum - Moon, Chuloo; Lee, Chang Hwan; Sang, Byoung-In; Um, Youngsoon (ELSEVIER SCI LTD, 2011)
Medium compositions favoring butanol and 1,3-propanediol (1,3-PDO) production from glycerol by Clostridium pasteurianurn DSM525 were investigated using statistical experimental designs. Medium components affecting butanol and 1,3-PDO production were screened using a fractional factorial experimental design. Among the six tested variables (phosphate buffer, MnSO4 center dot H2O, MgSO4 center dot 7H(2)O, FeSO4 center dot 7H(2)O, (NH4)(2)SO4, and yeast extract), FeSO4 center dot 7H(2)O, (NH4)(2)SO4, and yeast extract were found to be significant variables for further optimization of medium using a Box-Behnken design. Optimal butanol (0.98 g/L/h) and 1,3-PDO (1.19 g/L/h) productivities were predicted by the corresponding quadratic model for each product and the models were validated experimentally under optimized conditions. The optimal medium composition for butanol production was significantly different from that for 1,3-PDO production (0.06 vs. 0 g/L for FeSO4 center dot 7H(2)O, 7.35 vs. 0 g/L for (NH4)(2)SO4, and 5.08 vs. 8.0 g/L for yeast extract), suggesting that the product formation from glycerol by C. pasteurianum DSM525 can be controlled by changing medium compositions. (C) 2011 Elsevier Ltd. All rights reserved.